Research and Practice on Ideological and Political Teaching Reform of the “Data Mining” Course Based on the “Three-Integration and Three-Approach” Model - Cao, Qian; Jin, Yongchao (Journal of Research in Vocational Education, 2025)
With the rapid advancement of big data and artificial intelligence, the Data Mining course has become a core component of Data Science and Big Data Technology programs. Traditional teaching approaches, however, often overemphasize algorithms and techniques while overlooking value-oriented guidance and ideological education. This study applies the “Three-Integration and Three-Approach” model—integrating values, virtue, and enjoyment into teaching—to reform the ideological and political dimension of the course. By restructuring the syllabus, designing case-based content, innovating teaching methods, and establishing feedback mechanisms, a reform path was developed, characterized as “highlight-style, embedded-topic style, and element-fusion style.” Implemented at North China University of Science and Technology over three years, the reform significantly improved outcomes: the average course score rose from 76.2 to 84.7, the excellence rate increased from 21.1% to 48.9%, and the average ideological literacy score improved from 72.5 to 83.6, with the proportion of high-level students rising from 18.9% to 45.6%. These results demonstrate the effectiveness and scalability of the model, offering both practical experience and theoretical reference for advancing curriculum-based ideological and political education in higher education.